The Role of Sex Steroid Hormones in the Association Between Manganese Exposure and Bone Mineral Density: National Health and Nutrition Examination Survey 2013–2018 - Xiang Zhao; Jiayi Li; Jincong Yu; Yinhui Shi; Mengling Tang (Toxics)
This study investigates the association between blood Mn and bone mineral density (BMD), focusing on the mediating role of sex steroids, using data from 8617 participants in the National Health and Nutrition Examination Survey (NHANES) 2013–2018. Weighted multiple linear regression models were used to examine the association of blood Mn and total BMD, and mediation analyses were used to explored the roles of total testosterone (TT), estradiol (E2), and sex hormone-binding globulin (SHBG) in the Mn-BMD relationship, stratified by sex and menopausal status. Blood Mn was negatively associated with BMD in both sexes, with a pronounced effect in postmenopausal women. SHBG mediated 37.16% of the Mn-BMD association in men, whereas no mediating effects were found in women. E2 exhibited a significant indirect effect, suggesting that reduced E2 levels may amplify Mn’s effect on BMD. These findings indicate that Mn exposure is associated with decreased BMD, potentially through alterations in sex steroids, highlighting the importance of considering hormone status when evaluating the impact of Mn exposure on BMD.